Strategies for stress management: an analysis from the discipline of Guidance - Porras Quirós, Wilbert (2014)
The Guidance discipline and the schools’ supervision, both of themfocused on prevention as the key to anticipate the development of personal and social problems. The main objective of this study is to explore strategies for stress management in a group of students from LiceoNocturno Alfredo González Flores. It is performed by the premises of the naturalistic paradigm and has a phenomenological approach. This work concludes with the need to examine the subject in this population, because there are multiple stress agents such as maternity, study and work among the students.